EVALUATION OF THE EFFICACY OF NOVEL HERBAL TOPICAL ANESTHETIC GEL AND 2% LIGNOCAINE HYDROCHLORIDE GEL DURING THE ADMINISTRATION OF LOCAL ANESTHESIA IN CHILDREN: AN IN VIVO STUDY - ISHANI RAHATE; PUNIT FULZELE; NILIMA THOSAR; ANITA WANJARI; ANJORI RAUT; RIJUTA GUJAR; SHEPALI HULE (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: This study evaluates the effectiveness of a novel herbal topical anesthetic gel compared to conventional 2% lignocaine hydrochloride gel during local anesthesia administration in children. Methods: A randomized controlled trial with 42 children aged 5–14 years was conducted. Participants were divided into two groups (n=21 each): Group A received 2% lignocaine gel, and Group B received herbal gel. Pain response was measured using the Visual Analog Scale (VAS), sound eye motor (SEM) scale, and hedonic 9-point scale. An independent t-test was used for intergroup comparison. Results: The mean VAS scores were 5.67±1.32 for lignocaine and 5.19±0.87 for herbal gel (p=0.175). SEM scores were 3.19±0.75 for lignocaine and 2.95±0.86 for herbal gel (p=0.346), indicating no statistically significant differences in pain perception. However, the hedonic 9-point scale showed significantly higher taste acceptability for the herbal gel (5.86±1.15) compared to lignocaine (3.52±0.98), with a p<0.001. Conclusion: While both gels demonstrated similar efficacy in pain control, the herbal gel was significantly more palatable, suggesting it may be a more child-friendly alternative in pediatric dentistry.